Access to dynamic markets for small commercial farmers: the case of potato production in the Peruvian Andes - Escobal, Javier; Torero, Máximo (International Food Policy Research Institute, 2006)
The purpose of this study is twofold. On one hand, the objective is to assess the impact of new and more complex contracting schemes, as opposed to traditional marketing channels, on small farmers’ welfare. On the other hand, the study explores which may be the critical factors that determine the small farmers’ participation in these institutional arrangements. In this context, two critical factors are stressed. The first one has to do with access to credit and the second one is the size of the agricultural plot. In order to examine the decision of farmers to access the dynamic markets, the paper follows the study of Lapar et al (2003). The paper also follows impact evaluation techniques to identify the differences in the performance of farmers with access to dynamic markets and those without access. As it can be seen, in all cases, the difference between farmers with access and those without access is positive. This implies that having access to dynamic markets has positive impacts on the welfare of farmers. The results show that the farmers linked to the dynamic markets gain two cents of a dollar more per kilogram of potato. ...Our simulations showed that increase of their plot size to a minimum of five hectares (optimal size according to the industry) increases their sales to dynamic markets in 16%. However, the impact of new and more complex contracting schemes, as opposed to traditional marketing channels, could reduce significantly the access gap to dynamic markets by reducing transaction costs, increasing productivity, and increasing scale production through coordination of smallholders.